Metro sul do tejo: Service design and user feedback. Issue 4 (December 2016) - Lopes, Ana; Talavera, Guillermo; Domènech, Miquel
Highlights: Integrating seated areas in the tram environment, without directly changing tram stops, could be a good and affordable solution for frequented stations. Allowing users to charge their transport cards using ATM or home banking, would minimize the use of ticket-selling machines and frequency of maintenance. MST should be more demanding with employees, giving them proper training before they start contacting with the public. Abstract: Metro Sul do Tejo (MST) is a public Light rail system operating in Almada, Portugal. The line opened in 2008 with the aim of improving mobility in the city, reducing pollution, noise and traffic congestion, and reducing the use of private transport. The concession contract provided for the payment of compensations (to be paid by the State) if the estimated number of users was not achieved. After eight years in operation, the service is not economically viable without further support from the State, construction of second and third phases is suspended and the number of service users represents only 45 per cent of the initial estimate. The main purpose of this paper is to contribute to a better understanding of the causes behind such a low usage rate by analysing the results of a survey carried out among users of the MST. As we will see, the service does not fulfil quality expectations, nor does it satisfy important requirements such as safety and comfort, which are currently a cause for complaints and may prove decisive in increasing service usage and helping modal shift.